Predictive value of plasma neutrophil gelatinase-associated lipocalin in acute charcoal-burning carbon monoxide poisoning. (August 2019) - Moon, JM; Chun, BJ; Shin, MH; Cho, YS
This study aimed to assess the feasibility of using the plasma neutrophil gelatinase-associated lipocalin (NGAL) level at the time of presentation in the emergency department (ED) to predict acute kidney injury (AKI) and the long-term neurological outcomes of acute charcoal-burning carbon monoxide (CO) poisoning. This retrospective study included 260 patients who suffered acute charcoal-burning CO poisoning. The median plasma NGAL concentration at the time of presentation in the ED after acute charcoal-burning CO poisoning was 78 (54–115) ng/ml. The NGAL level was an independent predictor of AKI development and could be used to stratify the severity of AKI. However, the area under the receiver operating characteristic curve (AUC) of the predictive model for AKI that included both the plasma NGAL level and clinical parameters was comparable to that of the predictive model including only the clinical parameters. The plasma NGAL level at the time of presentation in the ED was an independent factor predicting long-term neurological outcomes in patients who did not develop AKI. In these patients, the plasma NGAL level significantly improved the predictive accuracy of the model when used in combination with clinical parameters. In contrast, the plasma NGAL level was not associated with long-term neurological outcomes in patients who developed AKI. Measurement of the plasma NGAL level at the time ED presentation might improve the prediction of long-term neurological outcomes in patients who do not develop AKI after acute charcoal-burning CO poisoning. However, it might not offer additional benefit for AKI prediction compared to previously used markers.